O vlogi rokopisov v dolgem prehodu iz rokopisne v tiskano knjigo v slovenski književnosti - Ogrin, Matija (Primerjalna književnost, 2017)
Numerous Slovenian texts written during the Baroque period of the seventeenth and eighteenth centuries have remained in manuscript form, because for a variety of reasons, both economic and ideological, they could not appear in the medium of the printed book. Yet many of these manuscripts are nonetheless variously connected with printed books: some were sewn into printed books as addenda. Because some manuscripts could not be published, their texts reached readers as manuscript publications. Yet other nineteenth-century manuscript texts published as manuscripts reproduced popular printed books that had come out in the Baroque period but could not be republished because of Enlightenment disapproval. This article explores the ways both media coexisted, with an emphasis on Slovenian letters in the early modern age, highlighting several special features of the manuscript medium. A manuscript enabled a scribe or a writer to considerably adapt its text not only to his linguistic idiom, but also to adapt, vary, and shorten a text, adding elements of oral tradition, according to his affinities and the needs of the local social context. He thus combined textual transmission of a manuscript (Textüberlieferung) with authorial creativity in a new text. During Slovenian letters% difficult and long transitional period from manuscript to the medium of the printed book, which lasted from the sixteenth until the middle of the nineteenth century, the manuscript was a medium that facilitated synthesis of copying texts and modifying and creating them.
Keywords: Age of Enlightenment; barok; Baroque; book history; codex book; Enlightenment; kodeksna knjiga; manuscripts; print book; razsvetljenstvo; rokopisi; Slovenian literature; slovensko slovstvo; tiskana knjiga; zgodovina knjige